HUBUNGAN PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK DENGAN PERTUMBUHAN ANAK TODDLER DI WILAYAH KERJA PUSKESMAS PERAMPUAN LOMBOK BARAT - Endah Sulistyani; Huswatun Hasanah; Nurhayati Hasanah; Ageng Abdi Putra (LPPM STIKES Mataram, 2025)
Introduction: The future of the nation is greatly influenced by the quality of children's growth, especially during the golden period of the first 1,000 days of life. Based on identification during the Posyandu visit, researchers found that many mothers did not utilize the Maternal dan Child Health Handbook and around 30 children still experienced abnormal growth in the Perampuan Community Health Center Work Area. The hope is that the Maternal and Child Health Handbook will be utilized more so that children's height and weight growth will be normal. In West Lombok, there are 65,566 children, and 65 children aged 24-36 months in the Perampuan Community Health Center Work Area. Nurses have a role as researchers who focus on identifying the use of Maternal and Child Health books and child growth. Objective: to determine the relationship between the use of MCH Handbook within and the growth of toddlers in the Parampuan Health Center area, West Lombok. Method:: This is a quantitative study with a population of 65 mothers with children aged 24-36 months. The sampling technique used was purposive sampling with 40 respondents. The method used was cross-sectional. The instrument for the utilization of the Maternal and Child Health Handbook was a questionnaire, and for growth, the Maternal and Child Health Handbook instrument was used. Results: The results of the study on the utilization of the Maternal and Child Health Handbook showed that 25 (63%) respondents were categorized as Good and 15 (37%) respondents were categorized as Poor. For growth, 26 (65%) children's height was Normal, 14 (35%) were Abnormal, and 25 (60%) children's weight was Normal, and 15 (40%) were Abnormal. The Spearman rank test showed a p-value >0.05 for both growth indicators, namely height (0.810) and weight (0.820). Conclusion: There is no relationship between the utilization of the Maternal and Child Health Handbook and the growth of toddlers at the Perampuan Community Health Center, West Lombok.